2020
DOI: 10.1111/tbj.13922
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome and toxicity from taxanes in breast cancer patients with BRCA1 and BRCA2 pathogenic germline mutations

Abstract: Germline variations in genes coding for proteins involved in the oxidative stress and DNA repair greatly influence drug response and toxicity. Because BRCA1 and BRCA2 proteins play a role in DNA damage repair, we postulated that taxane‐related toxicity is potentially higher and clinical outcome in different in patients with BRCA pathogenic variants (PV). Seven hundred nineteen women who underwent BRCA genetic testing and were treated with taxane‐containing chemotherapy for early‐stage breast cancer between 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…30 Other retrospective investigations including 31-150 patients addressed chemotherapy toxicity in other types of gBRCA1-2pv neoplasms. [23][24][25][26][36][37][38][39] Albeit mostly not reporting information on dose-intensity or treatment duration, these series apparently confirm our findings. Patients with breast cancer receiving anthracycline-and taxane-based chemotherapy had no difference in toxicity as opposed to wild-type patients.…”
Section: Esmo Opensupporting
confidence: 85%
See 2 more Smart Citations
“…30 Other retrospective investigations including 31-150 patients addressed chemotherapy toxicity in other types of gBRCA1-2pv neoplasms. [23][24][25][26][36][37][38][39] Albeit mostly not reporting information on dose-intensity or treatment duration, these series apparently confirm our findings. Patients with breast cancer receiving anthracycline-and taxane-based chemotherapy had no difference in toxicity as opposed to wild-type patients.…”
Section: Esmo Opensupporting
confidence: 85%
“…Patients with breast cancer receiving anthracycline- and taxane-based chemotherapy had no difference in toxicity as opposed to wild-type patients. 24 , 25 , 36 , 37 Only acute (i.e. after the first cycle) neutropenia increased without any impact on overall grade 3-4 maximum toxicity.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Fifteen of them were nested designs coming from randomized controlled trials (5 case controls 7 , 23 , 24 , 25 , 26 and 10 cohorts 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ), 17 were cohort studies, 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 and 10 were case‐control studies. 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 The studies were conducted in the United States (15 studies 24 , 26 , 27 , 31 , 34 , 35 , 36 , 42 , 48 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Whether BRCA variants increase the occurrence of myelosuppression in patients undergoing chemotherapy remains controversial. In their study on the toxicity of PTX-based chemotherapy in pathogenic BRCA variant carriers with breast cancer, Bayraktar et al ( 10 ) analyzed the hematological toxicity during PTX chemotherapy in a total of 790 patients of various BRCA mutation statuses and found that the occurrence of anemia and leukopenia in BRCA (–) patients was significantly higher than that in pathogenic BRCA variant carriers. Moreover, pathogenic BRCA2 variants were a predictor of hematological adverse reactions in breast cancer patients during PTX chemotherapy.…”
Section: Discussionmentioning
confidence: 99%